Holistic nursing clinical practice experiences of nursing students in medical‐surgical clinics: A qualitative study. Issue 3 (5th July 2021) - Kaya, Yunus; Kılıç, Sevcan T.; Öz, Fatma
Abstract: Purpose: This study was conducted to examine the experiences of nursing students in holistic nursing clinical practice. Design: Twenty senior nursing students participated in this study. Data were collected through focus group interviews with a qualitative approach followed by thematic data analysis. Findings: Four themes were obtained holistic care, barriers to holistic care, the contributions of holistic nursing internship, and students' expectations. Practice Implications: The participants stated that they believe that physical care is sufficient enough in the care they provide to patients and their families in clinical practice and that they only provide physical care. However, they stated that they became aware of the importance of holistic care with this practice and gained better insights into their professional requirements.